Statistical Assessment of Ukraine’s Agricultural Exports in the Conditions of the Russian-Ukrainian War - Sozanskyy, L. Yо. (Statistics of Ukraine, 2025)
Agricultural exports are one of the most important sources of foreign exchange in Ukraine, the adequacy of which in the conditions of modern challenges significantly depends on the socio-economic stability of the country, and also plays a significant role in the world market for agricultural products, in particular in the markets of the EU, Africa and Asia. However, the Russian war against Ukraine, and the geopolitical and geoeconomic factors associated with it, have caused significant structural and dynamic changes and risks to the rational and effective development of Ukraine’s agro-industrial exports. The study was carried out with the aim of identifying and providing a detailed description of the challenges facing the effective and rational (from the state’s perspective) development of Ukraine’s agricultural exports. To achieve the set goal, the study analytically substantiates that the highly specialized, raw material structure of Ukrainian commodity exports is irrational and economically inefficient. It has been established that one of the challenges to effective (from the state’s perspective) agricultural exports from Ukraine is the extremely low price of Ukrainian agricultural products on the world market. Proposals are made to strengthen the effectiveness of the Resolution of the Cabinet of Ministers of Ukraine “On Approval of the Procedure for Approval of Minimum Allowable Export Prices for Certain Types of Goods”. Trends and structural changes that have occurred as a result of geoeconomic and geopolitical transformations in the geographical structure of Ukraine’s agricultural exports (by sunflower oil, corn and wheat) are assessed. How Ukraine’s share in the geographical structures of imports (by sunflower oil, corn and wheat) of countries that are the main importers of agricultural products from Ukraine has changed has been analyzed. Based on the analytical conclusions obtained, the prospects for the economically rational development of Ukrainian agricultural exports are outlined.